BiOBr-MnO2 polymer film as well as preparation method and application thereof
By preparing BiOBr-MnO2 polymer film, using BiOBr-MnO2 composite catalyst and the composite technology of chitosan and PVDF film, the problem of low pure water flux in the PVDF film in the prior art is solved, and efficient dye wastewater treatment is achieved. Suitable for dye wastewater treatment in textile manufacturing and other industries.
Patent Information
- Application Number
- CN202411400466.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
Smart Images

Figure CN119281142A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane water treatment, and in particular relates to a BiOBr-MnO2 polymer membrane and a preparation method and application thereof. Background Art
[0002] In recent years, membrane separation technology for dye wastewater treatment has been continuously developed, providing a variety of strategies to meet the challenges posed by organic dyes in industrial wastewater. Separation membranes are a group of different barrier materials designed to selectively allow certain components in a mixture to pass through while blocking other components. According to their operating characteristics and applications, separation membranes can be divided into the following types: microfiltration membrane (MF), ultrafiltration membrane (UF), nanofiltration membrane (NF), reverse osmosis membrane (RO), catalytic separation membrane, etc. At present, among separation membranes, catalytic separation membranes have the most significant effect in treating wastewater.
[0003] In the prior art, the Chinese invention patent with application number CN202211007096.5 discloses a MnO2 nanowire-modified PVDF membrane, and its preparation method and application. The MnO2 nanowires are slowly added to the chitosan solution to form a precursor mixture, and the precursor mixture is filtered with a PVDF membrane to prepare a MnO2 nanowire-modified PVDF membrane. The stability of the MnO2 nanowire-modified PVDF membrane is greatly improved by utilizing the electrostatic interaction and chemical bond linking between chitosan, MnO2 nanowires and PVDF membrane. However, in the present application scheme, the PVDF membrane loaded only with MnO2 nanowires and chitosan has an average water contact angle of 32.5°, and an average pure water flux of only 248.5L / (m 2 h), which means that its energy consumption for processing the same amount of liquid is higher. Summary of the invention
[0004] Based on this, the present invention provides a BiOBr-MnO2 polymer membrane and a preparation method and application thereof, so as to solve the technical problem that the PVDF membrane only loaded with MnO2 nanowires and chitosan in the prior art has low pure water flux.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] A method for preparing a BiOBr-MnO2 polymer film, characterized in that it comprises the following steps:
[0007] S10. Prepare BiOBr-MnO2 composite catalyst for standby use;
[0008] S20. Prepare chitosan solution for later use;
[0009] S30. adding the BiOBr-MnO2 composite catalyst and the chitosan solution into distilled water, and ultrasonically dispersing the mixture to obtain a precursor mixture;
[0010] S40. Filtering the precursor mixture with a PVDF membrane to prepare a composite PVDF membrane;
[0011] S50. Drying the composite PVDF membrane to obtain a BiOBr-MnO2 polymer membrane.
[0012] Preferably, in the above-mentioned method for preparing the BiOBr-MnO2 polymer film, in step S10, the "preparing the BiOBr-MnO2 composite catalyst" comprises the following steps:
[0013] S11. adding bismuth nitrate pentahydrate to a nitric acid solution and stirring until completely dissolved, then adding MnO2 nanowires and ultrasonically dispersing them to obtain a mixed solution A;
[0014] S12. After the mixed solution A is placed in a water bath, cetyltrimethylammonium bromide solution is added and stirred evenly, and then the mixed solution B is slowly added and stirred to obtain a suspension;
[0015] S13. After centrifuging the suspension, filter, wash and dry to obtain the BiOBr-MnO2 composite catalyst.
[0016] Preferably, in the method for preparing the BiOBr-MnO2 polymer film, in step S11, the molar ratio of the bismuth nitrate pentahydrate to the nitric acid solution is (40 to 60):1.
[0017] Preferably, in the method for preparing the above-mentioned BiOBr-MnO2 polymer film, in step S11, the mass ratio of the bismuth nitrate pentahydrate to the MnO2 nanowires is (20 to 25):1.
[0018] Preferably, in the above-mentioned method for preparing the BiOBr-MnO2 polymer film, in step S12, the mixed solution B is a mixed solution of sodium hydroxide and sodium bromide, wherein the molar ratio of sodium hydroxide to sodium bromide is 3:2.
[0019] Preferably, in the method for preparing the above-mentioned BiOBr-MnO2 polymer film, the molar ratio of the bismuth nitrate pentahydrate to sodium bromide is 1:(50 to 70).
[0020] Preferably, in the method for preparing the BiOBr-MnO2 polymer film, in step S30, the mass ratio of chitosan in the chitosan solution to the BiOBr-MnO2 composite catalyst is 3:(300 to 1000).
[0021] Preferably, in the above-mentioned method for preparing the BiOBr-MnO2 polymer film, in step S30, the mass ratio of chitosan in the chitosan solution to the BiOBr-MnO2 composite catalyst is 3:700.
[0022] A BiOBr-MnO2 polymer film is prepared by the above-mentioned BiOBr-MnO2 polymer film preparation method.
[0023] An application of the BiOBr-MnO2 polymer membrane as described above in water treatment.
[0024] Compared with the prior art, the present invention has at least the following advantages:
[0025] The present invention adds BiOBr-MnO2 composite catalyst and chitosan solution into distilled water, ultrasonically disperses, obtains a precursor mixture, and filters the precursor mixture with a PVDF membrane to prepare a BiOBr-MnO2 polymer membrane. The BiOBr-MnO2 nanoparticles are fixed by chitosan to promote the composite of BiOBr-MnO2 particles and PVDF membrane. By using BiOBr-MnO2 as a catalyst, the pure water flux of the BiOBr-MnO2 polymer membrane is greatly improved, and the membrane treatment effect is excellent. Experiments show that the BiOBr-MnO2 polymer membrane prepared by this scheme has an average water contact angle of 21° and an average pure water flux of 632.68L / (m 2 ·h); the water flux of 30mg / L Congo red solution was 620.38L / (m 2 h), the rejection rate was 91.14%, and the water flux of this group of membranes for treating 90 mg / L Congo red solution was 431.00 L / (m 2 h), the interception rate is 99.38%. The BiOBr-MnO2 polymer membrane of the present application can be used for the treatment of industrial wastewater, especially dye wastewater in the textile manufacturing industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 SEM photos and physical pictures of BiOBr-MnO2 polymer membrane.
[0027] Figure 2 Water flux and contact angle of BiOBr-MnO2 polymer membrane.
[0028] Figure 3 This is the Zeta potential diagram of BiOBr-MnO2 polymer film.
[0029] Figure 4 Dye flux and retention rate of BiOBr-MnO2 polymer membrane.
[0030] Figure 5 The dye flux and retention rate of M-5 polymer membrane for Congo red solutions of different concentrations.
[0031] Figure 6 The dye flux and retention rate of M-5 polymer membrane for Congo red solution at different pH values.
[0032] Figure 7 This is a repeated practical test of the M-5 polymer membrane against Congo red solution. DETAILED DESCRIPTION
[0033] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The technical solution of the present invention will be further described below in conjunction with the embodiments of the present invention, and the present invention is not limited to the following specific implementation methods.
[0034] In a specific embodiment of the present invention, a method for preparing a BiOBr-MnO2 polymer film comprises the following steps:
[0035] S10. Prepare BiOBr-MnO2 composite catalyst for standby use;
[0036] S20. Prepare chitosan solution for later use;
[0037] S30. adding the BiOBr-MnO2 composite catalyst and the chitosan solution into distilled water, and ultrasonically dispersing the mixture to obtain a precursor mixture;
[0038] S40. Filtering the precursor mixture with a PVDF membrane to prepare a composite PVDF membrane;
[0039] S50. Drying the composite PVDF membrane to obtain a BiOBr-MnO2 polymer membrane.
[0040] In one specific embodiment, the “preparation of BiOBr-MnO2 composite catalyst” comprises the following steps:
[0041] S11. Add bismuth nitrate pentahydrate to a nitric acid solution and stir until completely dissolved, then add MnO2 nanowires for ultrasonic dispersion to obtain a mixed solution A; further, the molar ratio of the bismuth nitrate pentahydrate to the nitric acid solution is (40 to 60):1. The mass ratio of the bismuth nitrate pentahydrate to the MnO2 nanowire is (20 to 25):1. The MnO2 nanowire is a prior art product, and its preparation method is the same as the preparation method of the MnO2 nanowire in CN202211007096.5.
[0042] S12. After the mixed solution A is placed in a water bath, cetyltrimethylammonium bromide solution is added and stirred evenly, and then the mixed solution B is slowly added and stirred to obtain a suspension;
[0043] Furthermore, mixed solution B is a mixed solution of sodium hydroxide and sodium bromide, wherein the molar ratio of sodium hydroxide to sodium bromide is 3:2. In this step, because bismuth nitrate pentahydrate is hydrolyzed to produce BiONO3 and HNO3, which is strongly acidic, sodium bromide is added, BiONO3 exchanges with Br ions, and finally bismuth oxybromide is generated. Sodium hydroxide is added to neutralize the acidity to accelerate the reaction and nucleation, and the more small-sized bismuth oxybromide sheets are prepared, the more small-sized sheet structures accumulate to a certain number and are prone to self-assembly effect, agglomerating into a flower-like microsphere structure.
[0044] In a preferred embodiment, the molar ratio of bismuth nitrate pentahydrate to sodium bromide is 1:(50 to 70), further 1:60.
[0045] In another preferred embodiment, the volume ratio of the nitric acid solution, the hexadecyltrimethylammonium bromide solution and the mixed solution B is 1:(2 to 3):(2 to 3), further 1:2:3.
[0046] S13. After centrifuging the suspension, filter, wash and dry to obtain the BiOBr-MnO2 composite catalyst.
[0047] For example: First, weigh 4.851 g, 10 mmol, of bismuth nitrate pentahydrate, add it to 10.0 mL of 20.0 mmol / L nitric acid solution, stir it with a magnetic stirrer for 10 min at room temperature until the bismuth nitrate pentahydrate is completely dissolved, then add 0.24 g of MnO2 nanowires, and perform ultrasonic dispersion treatment for 10 min to obtain a mixed solution A.
[0048] Then, the mixed solution A was moved to a 70°C water bath and stirred for 2 minutes, and then 20 mL of 9 mmol / L hexadecyltrimethylammonium bromide solution was added and stirring was continued for 2 minutes; then 30 mL of the mixed solution B was slowly added dropwise, and stirring was continued for 10 minutes after the addition was completed to obtain a suspension.
[0049] Finally, the obtained suspension was poured into a centrifuge tube for centrifugation, and the precipitate was separated from the solution by suction filtration, and then the precipitate was washed alternately with distilled water and anhydrous ethanol for 3 to 5 times. The washed precipitate was placed in an oven preheated to 60°C and dried for 6 hours to finally obtain the BiOBr-MnO2 composite catalyst.
[0050] In some preferred embodiments, in step S30, the concentration of the chitosan solution is 10 mg / L, and the mass ratio of the chitosan solution to the BiOBr-MnO2 composite catalyst is 3: (3 to 7), preferably 3: 7. Specifically, the chitosan solution is prepared by first dissolving chitosan in an acetic acid solution to prepare a 4% chitosan solution, and then dissolving the chitosan in distilled water to obtain a 10 mg / L chitosan solution.
[0051] Then, 3 ml of chitosan solution and 7 mg of BiOBr-MnO2 were measured and added into a beaker containing 50 mL of distilled water, and ultrasonic dispersion was continued for 4.5 h to obtain a precursor mixture, and then step S40 was performed.
[0052] Step S40 is specifically to prepare to assemble the filter cartridge filter, apply a small amount of vaseline on the filter connection before operation to ensure its sealing performance; next, place the soaked polyvinylidene fluoride (PVDF) microporous filter membrane on the surface of the sand core, and use an iron clamp to fix the filter membrane and the filter, connect the rubber tube of the circulating vacuum pump to the glass sand core filter, and turn on the vacuum pump to start the filtration process; then, slowly pour the precursor mixture until the surface of the PVDF membrane is observed to be white and no water droplets are formed, wait for 1 minute, turn off the vacuum pump and remove the iron clamp, remove the PVDF membrane from the sand core, and place it in a culture dish.
[0053] Step S50 specifically includes placing the culture dish containing the PVDF membrane into an oven preheated to 60° C. and drying for 12 hours to obtain a BiOBr-MnO2 polymer membrane (referred to as polymer membrane).
[0054] In another specific embodiment of the present invention, a BiOBr-MnO2 polymer film is prepared by the above-mentioned method for preparing the BiOBr-MnO2 polymer film.
[0055] In another specific embodiment of the present invention, the above-mentioned BiOBr-MnO2 polymer membrane is used in water treatment, especially in the treatment of dye wastewater in the textile manufacturing industry.
[0056] The technical solution and technical effects of the present invention are further illustrated below through specific experimental examples.
[0057] 1. Experimental Materials and Equipment
[0058] 1.1 Raw materials and reagents
[0059] The reagents used in this experiment are shown in Table 1
[0060] Table 1 Reagents used in the experiment
[0061]
[0062]
[0063] 1.2 Experimental instruments
[0064] The instruments used in this experiment are shown in Table 2:
[0065] Table 2 Instruments used in the experiment
[0066] instrument model factory UV-Vis Spectrophotometer TU-1810 Beijing Puxi General Instrument Co., Ltd. Vacuum drying oven SCIZNTZ-10ND Nantong Jinshi Instrument Co., Ltd. refrigerator BCD-316WT Hisense (Beijing) Electronics Digital electric constant temperature water bath XMTD-204 Shanghai Boxun Industrial Co., Ltd. Centrifuge H-2010R Changsha Xiangyi Centrifuge Co., Ltd. Circulating water multi-purpose vacuum pump SHB-Ⅲ Zhengzhou Great Wall Science, Industry and Trade Co., Ltd. Ultrasonic cleaning machine KS-120EI Ningbo Haishu Kesheng Ultrasonic Equipment Co., Ltd. Electronic balance FA220 Shanghai Jingke Tianmei Scientific Instrument Co., Ltd. Glass sand core filter FD-JH-JS Puritch Instruments
[0067] 1.3 Characterization test instrument
[0068] Characterization of BiOBr-MnO2 polymer film performance: UV-visible absorption spectroscopy, scanning electron microscopy, contact angle tester, and Zeta potential measurement instrument.
[0069] First, the concentration of methylene blue solution can be quantitatively analyzed by UV-visible absorption spectroscopy. This method can effectively evaluate the removal efficiency of methylene blue by polymer membranes due to its high accuracy and simple operation, and thus indirectly reflect the treatment performance of the membrane.
[0070] Secondly, using a SIGMA500 scanning electron microscope (SEM), the surface and morphological features of the polymer membrane can be observed in detail. This information is crucial for understanding the filtration mechanism and performance of the polymer membrane, because the microstructure of the polymer membrane surface directly affects its filtration efficiency and durability.
[0071] Contact angle testing is an important tool for evaluating the hydrophilicity of polymer membrane surfaces. By measuring the size of the contact angle, we can not only determine the hydrophilicity or hydrophobicity of the material, but also further understand the changes in the chemical and physical properties of the membrane surface. In this experiment, the improvement of hydrophilicity means that the polymer membrane is easier to absorb water, which helps to improve its filtration efficiency.
[0072] Finally, the Zeta potential was measured to test the electronegativity of the BiOBr-MnO2 polymer membrane. The electronegativity of the membrane is crucial for the adsorption and removal of positively charged pollutants from water, so this test helps us better understand the electrochemical properties of the membrane and its potential ability to remove harmful substances from water.
[0073] 1.4 Study on the treatment of Congo red solution by BiOBr-MnO2 polymer membrane
[0074] 1.4.1 Calculation of water flux of BiOBr-MnO2 polymer membrane
[0075] The calculation formula of water flux is:
[0076]
[0077] Where: J is the water flux L / (m 2 ·h), V is the volume of water passing through the PVDF membrane in a certain period of time (L), A is the area of the PVDF membrane (m 3 ), Δt is the water penetration time.
[0078] 1.4.2 Calculation of BiOBr-MnO2 polymer membrane rejection and flux
[0079] In this experiment, since the Congo red dye used contains a small amount of water, before weighing the methylene blue sample, the wet weight of the dye needs to be weighed first. Next, in order to obtain the actual dry weight of Congo red, the dye containing water needs to be placed in an oven and dried at a constant temperature for 6 hours. After the drying is completed, the moisture content in the dye can be calculated based on the mass difference before and after drying, which will help to be more accurate when weighing next time, thereby reducing experimental errors.
[0080] Subsequently, a Congo red solution with a concentration of 30.0 mg / L was prepared according to the experimental requirements. In order to prevent the solution from changing due to the influence of light, the solution container needs to be covered with plastic wrap and fastened with a rubber band, and then the container should be properly stored in a dark environment. This can not only avoid the volatilization of the solution, but also prevent the chemical properties from changing due to light, ensuring the accuracy of the experiment and the stability of the solution. The retention rate (R%) and water flux of the five polymer membranes for Congo red solution were calculated by the following formulas:
[0081]
[0082] Where R (%) is the retention rate, cp and cf represent the concentrations of pollutants in the dye solution before and after penetration (mg / L), respectively.
[0083] This experiment is to calculate the flux and retention rate of five membranes for Congo red solution. In the experiment, 50mL of Congo red solution with a concentration of 30mg / L was first taken. According to previous experimental results, adding 1mL of hydrogen peroxide to the Congo red solution is not effective for catalytic degradation. Therefore, 2mL of hydrogen peroxide was chosen to be added in this experiment. It should be noted that if the amount of hydrogen peroxide added exceeds 2mL, it will cause a strong reaction, causing the membrane surface to become rough and even destroying the integrity of the membrane. After adding hydrogen peroxide, the catalytic degradation of the Congo red solution is achieved with the help of the BiOBr-MnO2 composite catalyst, and small molecules of carbon dioxide and water are finally generated. Through this process, the treatment effect of the membrane on the Congo red solution can be evaluated, thereby obtaining flux and retention rate data.
[0084] 1.4.3 Study on the treatment effect of BiOBr-MnO2 polymer membrane under different concentrations of Congo red solution
[0085] Based on the experiment of the treatment effect of different concentrations of Congo red solution, the polymer membrane with the best performance was selected for further testing. The test used 50mL of Congo red solution with concentrations of 10mg / L, 30mg / L, 50mg / L, 70mg / L, and 90mg / L, and 2mL of hydrogen peroxide was added in each test. These steps were used to evaluate the efficiency of polymer membrane in treating Congo red solution in different Congo red solution concentration environments.
[0086] 1.4.4 Study on the effect of BiOBr-MnO2 polymer membrane on the treatment of Congo red solution at different pH
[0087] In the Fenton system, pH value is one of the key parameters that determine the catalytic effect. In order to test the catalytic effect and the stability of the membrane, the polymer membrane needs to be placed in Congo red solutions with different pH values for dye wastewater separation tests. Specifically, sodium hydrogen phosphate dodecahydrate and citric acid are used to prepare solutions with pH values of 3, 5 and 7, respectively; and sodium hydroxide solutions with pH values of 9 and 11, respectively.
[0088] After the polymer membrane was tested for dye wastewater separation in the above-mentioned Congo red solution with different pH values, the water flux and retention rate were tested. The test used a Congo red solution with a concentration of 30 mg / L and a volume of 50 mL, and 2 mL of hydrogen peroxide was added in each test. These steps were used to evaluate the efficiency of the polymer membrane in treating Congo red solution in different pH environments.
[0089] 1.4.5 Reusability test
[0090] In order to evaluate the recyclability of this polymer membrane, the polymer membrane was recycled for vacuum filtration, and the state of the polymer membrane after six cycles as well as the retention rate and flux were observed to evaluate the reusability of the polymer membrane.
[0091] 2. Preparation of BiOBr-MnO2 polymer membrane
[0092] Preparation of BiOBr-MnO2 composite catalyst: First, weigh 4.851g, 10mmol of bismuth nitrate pentahydrate, add it to 10.0mL of nitric acid solution with a concentration of 20.0mmol / L, stir it for 10min at room temperature using a magnetic stirrer until the bismuth nitrate pentahydrate is completely dissolved, then add 0.24g of MnO2 nanowires (the preparation method of MnO2 nanowires is the same as CN202211007096.5), and ultrasonically disperse it for 10min to obtain a mixed solution A. Then, move the mixed solution A to a 70°C water bath and stir it for 2min, then add 20mL of a 9mmol / L hexadecyltrimethylammonium bromide solution, and continue stirring for 2min; then slowly add 30mL of mixed solution B (containing 90mmol NaOH and 60mmol NaBr) dropwise, and continue stirring for 10min after the addition is completed to obtain a suspension. Finally, the obtained suspension was poured into a centrifuge tube for centrifugation, and the precipitate was separated from the solution by suction filtration, and then the precipitate was washed alternately with distilled water and anhydrous ethanol for 3 to 5 times. The washed precipitate was placed in an oven preheated to 60°C and dried for 6 hours to finally obtain the BiOBr-MnO2 composite catalyst.
[0093] Preparation of chitosan solution: Measure 100 mL of 2% acetic acid solution, add 4 g of chitosan thereto, stir to form a homogeneous solution, and prepare a 4% chitosan solution; then measure 2.5 mL of 4% chitosan solution and dissolve it in 97.5 mL of distilled water to obtain a 10 mg / L chitosan solution.
[0094] Comparative Example 1
[0095] Polyvinylidene fluoride (PVDF) microporous filter membrane was used directly and was marked as M-1.
[0096] Comparative Example 2
[0097] 3 ml of chitosan solution was added to a beaker containing 50 ml of distilled water and ultrasonically dispersed for 4.5 h to obtain a precursor solution. Then, the precursor solution was loaded onto a PVDF membrane using vacuum filtration to obtain a polymer membrane M-2, which was then placed in an oven at 60 °C and dried for 12 h.
[0098] Experimental example
[0099] 3 ml of chitosan solution and a certain amount of BiOBr-MnO2 composite catalyst (see Table 3) were added to a beaker containing 50 mL of distilled water and ultrasonically dispersed for 4.5 hours to obtain a precursor solution. Then, the precursor solution was loaded onto a PVDF membrane using vacuum filtration to obtain polymer membranes labeled as M-3, M-4 and M-5, and the polymer membranes were placed in an oven at 60°C and dried for 12 hours.
[0100] Table 3 Five groups of polymer films with different BiOBr-MnO2 contents
[0101] name CS(mg) Catalyst (mg) M-1 0 0 M-2 3 0 M-3 3 3 M-4 3 5 M-5 3 7
[0102] 3. Performance test of BiOBr-MnO2 polymer membrane
[0103] 3.1 Scanning electron microscopy analysis of BiOBr-MnO2 polymer films
[0104] The BiOBr-MnO2 polymer membrane was tested by scanning electron microscopy. The SEM images and the actual membrane are shown in Figure 1 As shown:
[0105] Figure 1 a and Figure 1 b shows the scanning electron microscope (SEM) image of the polymer membrane. Through these images, it can be observed that the surface of the M-1 membrane has obvious wrinkles and unevenness. During the drying process of the membrane, when the drying temperature is high, the surface tension of the M-1 membrane surface increases, which leads to the formation of obvious wrinkles and unevenness on the membrane. And during filtration, the movement of the fluid and pressure changes may cause deformation of the membrane material, especially when the membrane material is brittle or the structure is weak, these force changes are more likely to cause wrinkles on the surface. In addition, no obvious pore structure was observed in the SEM image, which means that there is no channel for water circulation in the membrane. In comparison, Figure 1 c and Figure 1 d shows the SEM image of polymer membrane M-2, which has 3 mg of chitosan (CS) added to it. From the figure, we can see that the surface of M-2 has become more delicate, but similar to M-1, the addition of CS makes the membrane surface more dense. This indicates that even with the addition of CS, the pore formation of the membrane has not been significantly improved, which in turn affects the pore structure and surface smoothness of the membrane. From polymer membranes M-3 and M-4, it can be seen that after the addition of BiOBr-MnO2, the BiOBr-MnO2 composite catalyst is stacked on the surface of the membrane, making the polymer membrane have many more pores. The pore size of these pores is very small, which can block organic matter on the membrane, thereby achieving the effect of filtration and adsorption. From the picture of the M-5 polymer membrane, it can be seen that the micropores on the membrane are more dense and uniform, so that a better water flux is achieved while also having a higher retention rate.
[0106] 3.2 Contact angle analysis of BiOBr-MnO2 polymer film
[0107] By measuring the contact angles of five groups of membranes from M-1 to M-5, we can know whether the hydrophilic properties of the five groups of membranes are good, and plot the changing relationship between the contact angles and water fluxes of the five groups of polymer membranes (the unit of the contact angle is degree). The test results are shown in Table 4:
[0108] Table 4 Water flux and contact angle of BiOBr-MnO2 polymer membrane
[0109] Polymer film <![CDATA[Water flux (L / (m 2 ·h))]]> Contact angle (°) M-1 278.54 50 M-2 191.33 45 M-3 422.11 31.5 M-4 460.05 27 M-5 632.68 21
[0110] The contact angle reflects the hydrophilicity or hydrophobicity of the polymer membrane. A smaller contact angle (<90°) indicates that the membrane is hydrophilic and has a high affinity for water, which is beneficial to the water purification process because it promotes penetration and reduces dirt; a larger contact angle (>90°) indicates that the membrane is hydrophobic, which is important for gas separation processes and when handling organic solvents or oily substances. In other words, the size of the contact angle affects the transmission of materials across the membrane.
[0111] See also Figure 2 According to the experimental data, the contact angles of the five groups of polymer membranes are all less than 90°, which are hydrophilic materials. According to the experimental data, after adding BiOBr-MnO2, the contact angle of the polymer membrane gradually decreases, and the water flux gradually increases. As the amount of BiOBr-MnO2 gradually increases, the contact angle also decreases, and the water flux increases. Among them, the polymer membrane with the highest BiOBr-MnO2 content has the smallest contact angle and the highest water flux.
[0112] 3.3 Zeta potential analysis of BiOBr-MnO2 polymer membrane
[0113] Zeta potential measurements can provide insight into the surface charge of the membrane, which is a key factor in determining the interaction between polymer membranes and substances in solution (such as ions, colloids, and organic molecules). The selectivity of polymer membranes in separating charged substances may be affected by their Zeta potential. The electrostatic repulsion or attraction between the charged membrane surface and solutes can enhance or weaken the transport of ionic solutes.
[0114] The Zeta potential data of the polymer membrane tested in this experiment are as follows Figure 3 shown.
[0115] According to the Zeta potential measurement results of the five groups of membranes, it can be found that the M-1 polymer membrane exhibits a negative Zeta potential, which indicates that the ions on the surface of the M-1 polymer membrane are negatively charged; and for the M-2 polymer membrane, since it contains chitosan (CS), the amino groups contained in chitosan will be positively charged after protonation, so the Zeta potential of the M-2 polymer membrane is positive, showing obvious positive charge; the Zeta potentials of the other three groups of polymer membranes (M-3, M-4, and M-5) are also positive, indicating that the ions on their membrane surfaces are also positively charged.
[0116] Since the Congo red solution used in this article is an anionic dye, it interacts with the positively charged membrane surface and helps the adsorption of organic molecules. It is not difficult to see from the Zeta potential diagram that with the addition of BiOBr-MnO2, the Zeta potential of the polymer membrane gradually increases and remains positive. This means that with the increase of BiOBr-MnO2 content, the density of positive charges on the surface of the polymer membrane continues to increase, increasing the interaction with the anionic dye.
[0117] 3.4 Analysis of the effect of BiOBr-MnO2 polymer membrane on the treatment of different Congo red solutions
[0118] The above characterization analysis was performed on the five groups of polymer membranes. Through the above analysis, it can be seen that the performance of the M-5 polymer membrane is better than that of the other four groups of polymer membranes. In order to more intuitively reflect the performance of the five groups of polymer membranes, the five groups of polymer membranes were treated with Congo red solution respectively, and the experimental data obtained are shown in Table 5:
[0119] Table 5 Dye flux and retention rate of BiOBr-MnO2 polymer membrane
[0120]
[0121]
[0122] See also Figure 4 ,It can be seen from the experimental data that the retention rate of the M-5 polymer membrane is the highest among the five groups of polymer membranes. And by comparing the five groups of polymer membranes, it can be seen that with the increase in the amount of BiOBr-MnO2 used, the dye flux and retention rate of the polymer membrane will also increase, but when BiOBr-MnO2 is excessive, it will not affect the retention rate.
[0123] Analysis of the effect of 3.5M-5 membrane on the treatment of different Congo red solutions
[0124] Through the above characterization tests and the interception rate and water flux of Congo red solution, it can be seen that the M-5 polymer membrane has the best performance in terms of structure, performance and treatment effect on Congo red solution. Therefore, the M-5 polymer membrane was selected for further condition optimization, and the treatment effect of Congo red solution under different environments was further tested. Through further experiments, the interception rate and dye flux of the M-5 polymer membrane for Congo red solution of different concentrations were obtained. The data are shown in Table 6:
[0125] Table 6 Water flux and retention rate of M-5 polymer membrane for different concentrations of Congo red solution
[0126] Concentration (mg / L) Radius(cm) <![CDATA[Dye flux (L / (m 2 ·h))]]> Retention rate (%) 10 2.164 672.41 94.42 30 2.164 620.38 91.14 50 2.164 603.11 81.16 70 2.164 632.33 63.35 90 2.164 628.54 56.98
[0127] from Figure 5 It can be seen that with the increase of Congo red solution concentration, the retention rate of M-5 polymer membrane is gradually decreasing. The retention rate of 10mg / L solution is 94.42%, and when the concentration increases to 90mg / L, the retention rate drops to 56.98%. However, the dye flux did not decrease. All dye fluxes were within 600L / (m 2 h) The above results indicate that the membrane constructs excellent water channels through nanocatalysts.
[0128] Analysis of dye flux and retention rate of 3.6M-5 membrane at different pH
[0129] Generally speaking, dye wastewater is mostly acidic or alkaline. In order to explore the optimal pH value conditions for the treatment effect of M-5 polymer membrane on wastewater, the pH values were set to 3, 5, 7, 9, and 11. The optimal pH conditions were obtained by studying the interception rate and dye flux of Congo red solutions with different pH values. The experimental data are shown in Table 7:
[0130] Table 7 Dye flux and retention rate of Congo red solution by M-5 polymer membrane at different pH
[0131]
[0132]
[0133] from Figure 6 It can be seen that the M-5 polymer membrane has the best effect at pH 3, and the effect gradually worsens with the increase of pH. In summary, the M-5 polymer membrane works better under acidic conditions, but not ideal under neutral and alkaline pH conditions. This is because the Fenton-like reaction itself is more reactive under acidic conditions, but has very low reactivity under alkaline conditions, and the increase in pH causes the electropositivity of the membrane surface to decrease, thereby reducing the electrostatic interaction between the membrane and Congo red.
[0134] Analysis of the Repeatability of 3.7M-5 Membrane for Congo Red Solution
[0135] Through the study of the reusability of Congo red solution by M-5 polymer membrane, the following bar graph was drawn based on the experimental data ( Figure 7 ) to more intuitively demonstrate the reproducible practicality of the M-5 polymer film.
[0136] Table 8M-5 Repeated practicality test of polymer membrane for Congo red solution
[0137] frequency Retention rate (%) 1 91.14 2 91.14 3 90.89 4 90.89 5 89.94
[0138] from Figure 7 It can be seen that after five repetitive tests, the retention rate of the M-5 polymer membrane for the Congo red solution remained basically stable and did not change much, which further demonstrated that the M-5 polymer membrane has good reusability.
[0139] In summary, the present application prepares a BiOBr-MnO2 polymer membrane by adding a BiOBr-MnO2 composite catalyst and a chitosan solution into distilled water, performing ultrasonic dispersion, obtaining a precursor mixture, and filtering the precursor mixture with a PVDF membrane. The BiOBr-MnO2 nanoparticles are fixed by chitosan to promote the composite of the BiOBr-MnO2 particles and the PVDF membrane. By using BiOBr-MnO2 as a catalyst, the pure water flux of the BiOBr-MnO2 polymer membrane is greatly improved, and the membrane treatment effect is excellent. Five groups of polymer membranes were prepared by chitosan, a BiOBr-MnO2 composite catalyst and a PVDF microporous filter membrane. The degradation of the Congo red solution was achieved by a Fenton-like catalytic oxidation method using a heterojunction catalyst and catalytic degradation of hydrogen peroxide, thereby reflecting the performance of the polymer membrane. By testing the two important indicators of the polymer membrane interception rate and water flux, it was found that the water flux of the M-5 polymer membrane was 632.68L / (m 2 ·h), 30mg / L Congo red solution was selected to test five groups of polymer membranes, among which the water flux of M-5 polymer membrane was 620.38L / (m 2 h), the interception rate is 91.14%. Scanning electron microscopy shows that the addition of bismuth oxybromide / manganese dioxide can form micropores. Among the five groups of polymer membranes, the micropores of the M-5 polymer membrane are more regular; the contact angle test shows that among the five groups of polymer membranes, the hydrophilicity of the M-5 polymer membrane is the best. The Zeta potential test shows the electronegativity of the M-5 polymer membrane; by optimizing the conditions of the M-5 polymer membrane, it is verified that the reusability and stability of this membrane are excellent, and it is suitable for an environment with a pH of 3. These data further illustrate that the M-5 polymer membrane has excellent performance and better ability to treat organic dye wastewater.
[0140] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a BiOBr-MnO2 polymer film, characterized in that: The following steps are involved: S10. Prepare BiOBr-MnO2 composite catalyst for standby use; S20. Prepare chitosan solution for later use; S30. adding the BiOBr-MnO2 composite catalyst and the chitosan solution into distilled water, and ultrasonically dispersing the mixture to obtain a precursor mixture; S40. Filtering the precursor mixture with a PVDF membrane to prepare a composite PVDF membrane; S50. Drying the composite PVDF membrane to obtain a BiOBr-MnO2 polymer membrane.
2. The method for preparing the BiOBr-MnO2 polymer film according to claim 1, characterized in that: In step S10, the "preparation of BiOBr-MnO2 composite catalyst" comprises the following steps: S11. adding bismuth nitrate pentahydrate to a nitric acid solution and stirring until completely dissolved, then adding MnO2 nanowires and ultrasonically dispersing them to obtain a mixed solution A; S12. After the mixed solution A is placed in a water bath, cetyltrimethylammonium bromide solution is added and stirred evenly, and then the mixed solution B is slowly added and stirred to obtain a suspension; S13. After centrifuging the suspension, filter, wash and dry to obtain the BiOBr-MnO2 composite catalyst.
3. The method for preparing the BiOBr-MnO2 polymer film according to claim 2, characterized in that: In step S11, the molar ratio of the bismuth nitrate pentahydrate to the nitric acid solution is (40 to 60):
1.
4. The method for preparing the BiOBr-MnO2 polymer film according to claim 2, characterized in that: In step S11, the mass ratio of the bismuth nitrate pentahydrate to the MnO2 nanowires is (20 to 25):
1.
5. The method for preparing the BiOBr-MnO2 polymer film according to claim 2, characterized in that: In step S12, the mixed solution B is a mixed solution of sodium hydroxide and sodium bromide, wherein the molar ratio of sodium hydroxide to sodium bromide is 3:
2.
6. The method for preparing the BiOBr-MnO2 polymer film according to claim 5, characterized in that: The molar ratio of the bismuth nitrate pentahydrate to the sodium bromide is 1:(50 to 70).
7. The method for preparing the BiOBr-MnO2 polymer film according to claim 1, characterized in that: In step S30, the mass ratio of chitosan in the chitosan solution to the BiOBr-MnO2 composite catalyst is 3:(300 to 1000).
8. The method for preparing the BiOBr-MnO2 polymer film according to claim 7, characterized in that: In step S30, the mass ratio of chitosan to the BiOBr-MnO2 composite catalyst in the chitosan solution is 3:
700.
9. A BiOBr-MnO2 polymer film, characterized in that: The BiOBr-MnO2 polymer film is prepared by the preparation method of any one of claims 1 to 8.
10. Use of the BiOBr-MnO2 polymer membrane according to claim 9 in water treatment.
Citation Information
Patent Citations
MnO2 nanowire-modified PVDF film, its preparation method and application
CN115475539B
Cited By
Method for in-situ preparation of bismuth oxyhalide-PVDF-based composite solid electrolyte membrane
CN119764551A